2017
DOI: 10.1017/s0033291716003068
|View full text |Cite|
|
Sign up to set email alerts
|

Genetic influences on hormonal markers of chronic hypothalamic–pituitary–adrenal function in human hair

Abstract: Background Cortisol is the primary output of the hypothalamic-pituitary-adrenal (HPA) axis and is central to the biological stress response, with wide-ranging effects on psychiatric health. Despite well-studied biological pathways of glucocorticoid function, little attention has been paid to the role of genetic variation. Conventional salivary, urinary, and serum measures are influenced by diurnal variation and transient reactivity. Recently developed technology can be used to measure cortisol accumulation ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
27
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 60 publications
(101 reference statements)
3
27
1
Order By: Relevance
“…Twin studies have demonstrated the heritability of basal salivary cortisol (Bartels, Geus, Kirschbaum, Sluyter, & Boomsma, 2003;Ouellet-Morin et al, 2008) and animal studies have indicated the heritability of HCC in monkeys (Fairbanks et al, 2011). Recently, the first genetic study examining the role of genetic variation of long-term cortisol exposure revealed that genetic factors accounted for about half the variation in HCC (Tucker-Drob et al, 2017). Thus, the relation of parent and child HCC may be due, in part, to shared genetic alleles.…”
Section: Parent and Child Hair Cortisolmentioning
confidence: 99%
“…Twin studies have demonstrated the heritability of basal salivary cortisol (Bartels, Geus, Kirschbaum, Sluyter, & Boomsma, 2003;Ouellet-Morin et al, 2008) and animal studies have indicated the heritability of HCC in monkeys (Fairbanks et al, 2011). Recently, the first genetic study examining the role of genetic variation of long-term cortisol exposure revealed that genetic factors accounted for about half the variation in HCC (Tucker-Drob et al, 2017). Thus, the relation of parent and child HCC may be due, in part, to shared genetic alleles.…”
Section: Parent and Child Hair Cortisolmentioning
confidence: 99%
“…Second, the hair cortisol differences might reflect genetic differences in subpopulations (population stratification). For example, since hair color is strongly linked to genetic ancestry, it might be a marker of genetic variations related to cortisol metabolism or sensitivity 3 . Third, color might be a marker for minority status and the related stress, which would explain higher systemic cortisol levels 1 , 2 , 4 .…”
Section: Introductionmentioning
confidence: 99%
“…Also, genes associated with an increased risk of adrenal suppression in children using glucocorticosteroids have been localized. 6,32 Genotyping might further clarify the relation between corticosteroids and adrenal function. However adrenal function tests will still be needed when suspecting a case of adrenal insufficiency.…”
Section: Discussionmentioning
confidence: 99%